Design of a composite nose wheel for commercial aircraft. Issue 1 (January 2021) - Wacker, J-D; Laveuve, D; Contell Asins, C; Büter, A
Abstract: Innovative approaches for lightweight design of components can contribute significantly to reduced fuel consumption and emissions of future aircraft. Within the framework of the European aviation research program Clean Sky 2, an innovative design of an aircraft nose wheel for the A320 is developed using carbon fiber reinforced plastics (CFRP) in order to demonstrate a weight reduction potential of 27% compared to conventional designs. In the present paper, the approach of the development process and the final detailed design of the composite aircraft wheel as well as a manufacturing concept are presented, various design challenges are highlighted and the solutions developed to meet them are discussed. Within a concept phase different structural design principles for the wheel are analyzed, taking into account the challenging load cases during different phases of aircraft operation. The selected innovative design principle is further elaborated into a detailed design considering design challenges such as space, installation, and safety requirements, as well as integration of bearings, seals and joint solutions. Also, structural analysis of the composite components via FEA and experimental validation of the joints are discussed. In addition, the manufacturing concept for the complex wheel geometry via resin transfer molding (RTM) using carbon non-crimp fabrics is presented and an outlook on the future manufacturing and testing of wheel prototypes is given.